The Research on A Fifth-Years Old Child with His Kinds of Language (Foreign Language, Mother Tongue, and Second Language): A Case Study on Muhammad Joko Purnomo - Eka Tri Wulandari (Attractive : Innovative Education Journal, 2024)
The article was to explain about a fifth-years old child with his kinds of language (first language, foreign language, mother tongue, and second language); A case study on Muhammad Joko Purnomo. The aims to this research are describe below to deeply find out the ways of child get the first language, foreign language, and mother tongue. The research is also aimed to have a brief knowledge about the ways of child learn the second language. The researchers used qualitative method. A case study will be used on this research to provide deeper understanding regarding joko`s first language, foreign language, mother tongue, and second language process. Used for analyzing result data from the kinds of natural observation which is in natural setting of home, school and other places. The researcher had in-depth interview with joko, which has documentation for some time. Results research conducted got results that the second language acquisition was influenced by smallest local level (family), the research may contribute to the re-thinking and re-design of English second language acquisition process in the in the family situation. The research also demonstrated by the case study of Muhammad Joko Purnomo as a student of kindergarten ketapang 0505 Cipondoh. Joko’s first language acquisition is Javanese and Bahasa. As well as results, in learner’s characteristic, Joko is introvert and shy boy. However, his parent teaches his about independent. In learning condition, his school supports his first and second language acquisition. Above all, this research expected that the research will be followed with research to see his process of first language, foreign language, mother tongue, and second language.